Serbia and foreign direct investments - Budimir Branka (Trendovi u Poslovanju)
The basic element of the process of privatization as the inevitable product of the transition process is the capital, expectedly. Capital is a prerequisite for a country to transform state property into a private one. As is the case with most countries that have gone through the transition process, Serbia was unable to perform the privatization process by herself namely, she missed capital of her own. In this case, the only solution was foreign capital and foreign investment. The most important effect for Serbia was made by direct investments, which is to be discussed in the text to follow.